Between Reform and Dependency: IFI Influence on Egyptian Food Sovereignty - Ayman Abouelfarh, Nayera (AUC Knowledge Fountain, 2026)
This thesis examines how international financial institutions (IFIs), particularly the International Monetary Fund (IMF) and the World Bank, have influenced Egyptian food sovereignty between 2016 and 2024. It asks how IFI-backed structural adjustment programs, policy influence, and ideational influence reshaped Egyptian public policy and affected the state’s capacity to autonomously manage its food system. The thesis argues that IFI-driven reform agendas prioritized macroeconomic stabilization, fiscal discipline, and export-oriented growth over food sovereignty, increasing Egypt’s external dependence and vulnerability to global market shocks. Methodologically, the study employs a qualitative comparative case study design combining process tracing and thematic document analysis using MAXQDA. The analysis is based on IMF and World Bank reports, Egyptian policy documents, legislation, and macroeconomic and agricultural data. The empirical analysis is structured around three policy domains: state governance of food subsidies and price controls; trade, foreign exchange policy, and import dependence; and domestic agricultural production and procurement. The findings demonstrate that IFI- backed reforms constrained the state’s capacity to regulate food access, intensified dependence on imports and foreign exchange, and promoted export-oriented agricultural policies without resolving structural food dependency. The thesis concludes that food sovereignty in Egypt has been increasingly shaped by global financial governance and neoliberal reform paradigms, limiting the state’s autonomous control over its food system.